Beyond Leaders and Followers: Understanding Participation Dynamics in Event-Based Social Networks. Issue 20 (14th December 2019) - Chen, Jiawei; Wang, Xiying; Beck, Jordan; Wu, Chuqing; Carroll, John M.
ABSTRACT: Understanding user behaviors and social relations in social media has been an important topic in Human-Computer Interaction research. In this paper, we look at an emerging form of social media, Event-based Social Networks (EBSNs), which support a special type of hybrid community where people are connected online to organize themselves for offline gatherings. EBSN users are labeled as either organizers or members on existing platforms, and their behavioral and relationship patterns in offline events have not been described systematically. To understand participation dynamics in EBSNs, we present an interview study with 12 Meetup users and categorize a variety of social roles beyond organizers and members. We identify that different types of organizers, classical leaders and delegated leaders, have different relationship patterns with various types of members, including active contributors, active followers, newcomers and occasional visitors. By comparing these roles with purely offline or online communities, we discuss how participation dynamics in EBSNs reflect the intertwined impacts of hybrid community and implications of our findings for technology designs.